A blockchain architecture with master-slave blockchain - Pengliu TAN; Lixuran WAN (物联网学报)
With the continuous development of blockchain technology, different chains are derived due to different adaptation scenarios.Each chain has its own characteristics, such as public chains like bitcoin and ethereum, a large number of private chains and alliance chains.But as far as the current Internet is concerned, the implementation of many application scenarios on traditional blockchains has become particularly inconvenient.A master-slave blockchain (MSBC) architecture was proposed, which was mainly composed of a master block, a subordinate master block and a subordinate micro block.The master chain was composed of master blocks.Each master block has a slave master block and multiple slave micro block on its side chain.In addition, the master block and the master block were directly connected by the Hash of the previous block, the master block and the slave master block were connected by the Hash of the unique information, and the slave micro block and the previous block (whatever the slave master block or the slave micro block) was also connected by the Hash of the previous block.In talent chain, this kind of structure could put a person’s fixed resume information on the master chain, but updated resume information constantly on the slave side chain.MSBC architecture was more scalable, and it could improve the efficiency of data query.The experimental results show that the framework in the similar applications such as talent chain is feasible and the query efficiency has been improved greatly.